Chronic age-related diseases share risk factors: do they share pathophysiological mechanisms and why does that matter? (Swiss Medical Weekly, 2010)
The World Health Organization (WHO) assigns high priority to the prevention of non-communicable age-related diseases such as heart disease, cancer, diabetes, stroke and chronic lower respiratory diseases. They are now the leading causes of death, in both industrialised and developing countries, mostly due to increased life expectancy and urbanisation with associated changes in lifestyle and environment. Tobacco smoking, physical inactivity and resulting obesity are established risk factors for many chronic diseases. Yet, the aetiology of age-related diseases is complex and varies between individuals. This often makes it difficult to identify causal risk factors, especially if their relative effects are weak. For example, the associations of both obesity and air pollution with several age-related diseases remain poorly understood with regard to causality and biological mechanisms. Exposure to both, excess body fat and particulate matter, is accompanied by systemic low-grade inflammation as well as alterations in insulin/insulin-like growth factor signalling and cell cycle control. These mechanisms have also been associated in animal and some human studies with longevity and ageing in more general terms. In this paper, it is therefore hypothesised that they may, at least in part, be responsible for the adverse health effects of obesity and air pollution. It is argued that molecular and genetic epidemiology now offer novel instruments to improve the understanding of these pathophysiological pathways and their link to disease aetiology. Understanding the causality of exposure disease associations and differences in susceptibilities to environment and lifestyle is an important aspect for effective prevention.